Recurrent Rhabdomyolysis Induced by Severe Hypothyroidism - Boryushkina, Varvara (Cureus, 2019)
Hypothyroidism is frequently associated with myalgias, muscle stiffness, easy fatigability, and occasionally some degree of myopathy with mildly elevated muscle enzymes. Rarely, hypothyroidism may be complicated by rhabdomyolysis, the rapid destruction of skeletal muscle with myoglobin, creatine kinase, urate, and electrolytes release into the circulation. Recurrent cases of rhabdomyolysis are uncommon as most patients experience only one episode of rhabdomyolysis in their lifetime. Most common causes of such episodes are trauma, epileptic seizures, or medication. We describe a case of a 49-year-old male with a history of hypothyroidism, who repeatedly developed severe rhabdomyolysis precipitated by deep muscle injury, seizure, and poor medication compliance. Interestingly, he never developed any of the complications of rhabdomyolysis despite high levels of serum creatine kinase. The most common and feared complication of rhabdomyolysis is acute kidney injury which can occur in 15 to 50% of patients with rhabdomyolysis. Timely and appropriate fluid resuscitation is the mainstay therapy for acute kidney injury (AKI) prevention. Recurrent rhabdomyolysis in a patient should prompt further investigation if there is a family history of a neuromuscular disorder or exercise intolerance. In a case of refractory hypothyroidism, a patient should be counseled on proper regimen and medication compliance.